(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research aims to develop a GPS Tracking and Digital Reporting system to support field personnel monitoring and operational report management at the Tulungagung Police. The research uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, system design, application development, implementation, and evaluation. In the analysis stage, user needs were identified through observation and interviews, followed by the design of a web-based and mobile system architecture. The development results in a system consisting of a web dashboard for administrators and a mobile application for field personnel that are integrated in real-time. The main features that were successfully developed include real-time personnel location tracking, patrol instruction and schedule management, digital reporting with photo and video support, location checkpoints, and automatic report generation. The implementation results show that all main functions of the system can run according to the operational needs of the Tulungagung Police and support monitoring of personnel activities more effectively, accurately, and documented. These findings indicate that the developed system has the potential to improve the efficiency of field supervision and the quality of police operational report management.